Antiviral mechanism of preclinical antimalarial compounds possessing multiple antiviral activities. Issue 5 (4th March 2021) - Gu, Weilin; Ueda, Youki; Dansako, Hiromichi; Satoh, Shinya; Kato, Nobuyuki
Abstract: We previously found that N‐89 and its derivative, N‐251, which are being developed as antimalarial compounds, showed multiple antiviral activities including hepatitis C virus (HCV). In this study, we focused on the most characterized anti‐HCV activity of N‐89(N‐251) to clarify their antiviral mechanisms. We first prepared cells exhibiting resistance to N‐89(N‐251) than the parental cells by serial treatment of HCV–RNA‐replicating parental cells with N‐89(N‐251). Then, we newly generated HCV–RNA‐replicating cells with the replacement of HCV–RNAs derived from N‐89(N‐251)‐resistant cells and parental cells. Using these cells, we examined the degree of inhibition of HCV–RNA replication by N‐89(N‐251) and found that the host and viral factors contributed almost equally to the resistance to N‐89(N‐251). To further examine the contribution of the host factors, we selected several candidate genes by cDNA microarray analysis and found that the upregulated expression of at least RAC2 and CKMT1B genes independently and differently contributed to the acquisition of an N‐89(N‐251)‐resistant phenotype. For the viral factors, we selected several mutation candidates by the genetic comparative analysis of HCV–RNAs and showed that at least one M414I mutation in the HCV NS5B contributed to the resistance to N‐89. Moreover, we demonstrated that the combination of host factors (RAC2 and/or CKMT1B) and a viral factor (M414I mutation) additively increased the resistance to N‐89. In summary, we identified the host and viral factors contributing to the acquisition of N‐89(N‐251)‐resistance in HCV–RNA replication. These findings will be useful for clarification of the antiviral mechanism of N‐89(N‐251).